Antenatal magnesium sulphate for preventing cerebral palsy: An economic evaluation of the impact of a quality improvement program. (29th November 2021) - Keir, Amy; Rumbold, Alice; Shepherd, Emily; Mcintyre, Sarah; Groves, Charlotte; Cavallaro, Angela; Crowther, Caroline; Callander, Emily
Abstract : Previous work demonstrated that implementing a quality improvement (QI) program improves the uptake of guideline‐recommended antenatal magnesium sulphate, a critical intervention known to reduce cerebral palsy risk. Here we estimate potential cost savings attributable to the improved uptake. By expanding coverage from 63 to 83% of eligible women, we estimated that five children potentially would not have received a diagnosis of cerebral palsy, a potential cost saving of $AU4.8 million in lifetime healthcare costs. Our findings strengthen the case for embedding QI approaches in perinatal care to reduce the incidence of cerebral palsy.